Effect of Sertraline on C-Reactive Protein Serum Levels in Hemodialysis Patients - Rehman, Misbah; Ahmad, Yahya Azeem; Shahid, Zarwa; Naeem, Iqra; Jamil, Muhammad Irfan; Ahmed, Adeel; Abbas, Ghulam (Indus Journal of Bioscience Research, 2025)
Background and Aims: Depression and systemic inflammation are prevalent and interlinked in patients undergoing maintenance hemodialysis, contributing to adverse outcomes including poor treatment adherence, cardiovascular complications, and increased mortality. This study aimed to evaluate the effects of sertraline on serum high-sensitivity C-reactive protein (hs-CRP) levels and depressive symptoms among hemodialysis patients diagnosed with major depressive disorder. Materials and Methods: A randomized, double-blind, placebo-controlled trial was conducted at Nishtar Hospital Multan with 62 adult hemodialysis patients diagnosed with major depressive disorder. Participants received either sertraline (25–100 mg/day) or placebo for 12 weeks. Primary outcome was change in hs-CRP levels; secondary outcomes included HAM-D score changes, remission rates, and adverse events. CRP was measured pre-dialysis via immunonephelometric assay. Results: Both groups showed balanced baseline characteristics with mean ages of 46.4±11.2 and 47.8±10.7 years respectively. Baseline CRP levels were similar between sertraline (6.5±2.8 mg/L) and placebo groups (6.7±2.9 mg/L). After 12 weeks, the sertraline group demonstrated significant CRP reduction from 6.5±2.8 to 4.2±2.1 mg/L (mean change: -2.3±1.1 mg/L, p<0.001), while placebo showed minimal change (-0.5±0.8 mg/L, p=0.08). Between-group difference was statistically significant (-1.8 mg/L, 95% CI: -2.4 to -1.2, p<0.001). CRP normalization occurred in 72.4% of sertraline patients versus 26.7% in placebo group. Depression scores improved significantly more with sertraline (HAM-D reduction: -7.1±2.8) compared to placebo (-3.1±2.9, p<0.001). Conclusion: Sertraline significantly reduced systemic inflammation and depressive symptoms in hemodialysis patients. These findings support its dual role in managing depression and inflammation in end-stage renal disease.